2022
DOI: 10.1186/s40164-022-00321-x
|View full text |Cite|
|
Sign up to set email alerts
|

Unraveling the structures, functions and mechanisms of epithelial membrane protein family in human cancers

Abstract: Peripheral myelin protein 22 (PMP22) and epithelial membrane proteins (EMP-1, -2, and -3) belong to a small hydrophobic membrane protein subfamily, with four transmembrane structures. PMP22 and EMPs are widely expressed in various tissues and play important roles in cell growth, differentiation, programmed cell death, and metastasis. PMP22 presents its highest expression in the peripheral nerve and participates in normal physiological and pathological processes of the peripheral nervous system. The progress of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 146 publications
0
2
0
Order By: Relevance
“…Inferred B1 cells genes Atf3, Riiad1, Foxj1, Gadd45b, Emp1, and Tagln2 were expressed in B1 and ependymal cells in the VZ, had low or no expression in B2 cells in the SVZ and the wedge (Figures 4J, K and S5A). An exception was Emp1, which is upregulated during mitosis 48 , was present in dividing cells in the SVZ, including the wedge (Figure S5A). We confirmed that Atf3, Riiad1, Foxj1, Gadd45b, Emp1, and Tagln2 were expressed in B1 cells by using RNAscope in en face sections of the ventricular wall and co-stained with ß-catenin and γ-tubulin to identify B1 cells’ apical contact.…”
Section: Resultsmentioning
confidence: 99%
“…Inferred B1 cells genes Atf3, Riiad1, Foxj1, Gadd45b, Emp1, and Tagln2 were expressed in B1 and ependymal cells in the VZ, had low or no expression in B2 cells in the SVZ and the wedge (Figures 4J, K and S5A). An exception was Emp1, which is upregulated during mitosis 48 , was present in dividing cells in the SVZ, including the wedge (Figure S5A). We confirmed that Atf3, Riiad1, Foxj1, Gadd45b, Emp1, and Tagln2 were expressed in B1 cells by using RNAscope in en face sections of the ventricular wall and co-stained with ß-catenin and γ-tubulin to identify B1 cells’ apical contact.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, TMCC1 was significantly downregulated in PE placentae compared with normal placentae [32]. EMP1 is a protein-coding gene involved in apoptosis, which negatively regulates cell growth [33]. Circulating EMP1 was positively associated with severe placental insufficiency, placental dysfunction, and fetal growth restriction [34].…”
Section: Upregulated Genes With High Betweennessmentioning
confidence: 99%